Method for obtaining nanoscale nitride fluorescent material

By using non-stoichiometric raw materials and oxalic acid solution ultrasonic treatment methods in Mini LED display technology, nano-scale nitride fluorescent materials were prepared, which solved the problems of unstable luminous performance and chromatic aberration caused by the small size of Mini LED chips, and achieved efficient and stable Mini LED display effect.

CN119736086AActive Publication Date: 2025-04-01XIAMEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411982319.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In Mini LED display technology, due to the small size of Mini LED chips, the number of particles of traditional fluorescent material is reduced, resulting in unstable luminous performance and chromatic aberration problems.

Method used

Using non-stoichiometric raw materials and oxalic acid solution sonication method, nano-scale nitride fluorescent materials with a median D50 particle size of 80 nm to 100 nm were prepared under high temperature sintering and grinding.

Benefits of technology

It realizes the stable light emission performance and color consistency of Mini LED devices, and the quantum efficiency is between 50% and 70%, meeting the high-performance needs of Mini LED display modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736086A_ABST
    Figure CN119736086A_ABST
Patent Text Reader

Abstract

A method for obtaining a nanoscale nitride fluorescent material belongs to the field of fluorescent materials, and comprises the following steps: uniformly mixing CamSi alloy, EuSi alloy and AlN powder according to a molar ratio of (1-x): x: 1 in a protective atmosphere, carrying out high-temperature sintering and grinding treatment in an ammonia atmosphere, mixing with an oxalic acid solution, and carrying out ultrasonic treatment, filtration and drying; according to the nanoscale nitride fluorescent material CaxEu1-xAlSiN3, x is larger than or equal to 0.02 and smaller than or equal to 0.08, and the D50 median particle size ranges from 80 nm to 100 nm. Under the excitation of 450 nm light, the main peak of the emission spectrum is 670-710 nm, and the quantum efficiency is 50-70%. In the preparation steps, non-stoichiometric raw materials are specially adopted to prepare the nanoscale nitride fluorescent material, and the nanoscale nitride fluorescent material for Mini LED device packaging is obtained under the synthesis conditions that the synthesis conditions are mild and a ball milling process is not adopted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fluorescent materials, and in particular to a method for obtaining nano-level nitride fluorescent materials. Background Art

[0002] Mini LED display technology is a new type of backlight technology that uses a light-emitting chip with a planar size between 50 μm and 200 μm, which is smaller than traditional LEDs. This means that more LED units can be integrated in the same area, and Mini LED display technology has higher resolution, brightness, contrast, and wide color gamut. As we all know, traditional LED packaging technology is to mix fluorescent materials (particles) with silica gel and then apply them to the surface of the LED chip. The size of traditional LED chips is generally millimeter-level, and the fluorescent materials encapsulated on the LED chips are mostly synthesized using high-temperature solid-phase synthesis technology, such as document 1 (Haohao Wang, Yujie Liu, Xudong Zhu, Liangshu Wei, Xiping Jiang, Yong Chen, Langkai Li, Preparation of CaAlSiN3:Eu 2+ As disclosed in "Red-emitting phosphor by a two-step method for solid-state lighting applications, Ceramics International, 2020, 46, 14: 23035-23040", its D50 median particle size is generally ~10 μm. This means that for millimeter-level traditional LED chips, the number of fluorescent material particles packaged on the chip is considerable, in the tens of thousands (millimeter-level chips versus ~10 μm fluorescent material particles). In this way, even if there are differences in luminous properties between fluorescent material particles, in a statistical sense, the difference in luminous properties between particles has no decisive influence on the performance of the final LED package. That is, for traditional LED packages, the particle size of the fluorescent material has little effect on the final luminous performance of the LED product.

[0003] However, for Mini LED display technology, since the planar size of Mini LED chips is between 50 μm and 200 μm, when encapsulated with fluorescent materials with a D50 median particle size of ~10 μm, the number of fluorescent material particles encapsulated on the Mini LED chip is sharply reduced to hundreds (micron-level chips vs. fluorescent material particles of ~10 μm). At this time, the difference in luminous performance between the fluorescent material particles will cause the luminous performance of the encapsulated single Mini LED device to fluctuate, and ultimately cause color differences between the Mini LED display modules composed of multiple Mini LED devices. In order to ensure the performance of Mini LED display devices, it is obviously a more feasible method to reduce the D50 median particle size of the fluorescent material without changing the size of the Mini LED chip.

[0004] The method of reducing the D50 median particle size of fluorescent materials can be ball milling to grind the existing fluorescent materials with a D50 median particle size of 10 μm to submicron or nanometer level. For example, Document 2 (Li Shuxing, Xie Rongjun, A high brightness, high external quantum efficiency red mini-LED and its preparation method, CN114447190A) discloses a method of preparing micro-nano red fluorescent materials by ball milling, centrifugation and acid washing. Finally, the (Sr, Ba)2Si5N8:Eu commercial nitride red fluorescent powder with a D50 of 11.5 μm can be ball milled to a D50 median particle size of 0.1 μm. However, it should be pointed out that, as disclosed in Document 3 (Liu Qingling, Jiang Kuiming, a method for preparing a ball-milling-free, spherical crystal phosphor, CN100554364C) and Document 4 (Lei Lixu, Gao Xiaorui, a fluorescent material for converting ultraviolet light into red light and a method for preparing the same, CN100489055C), the ball milling process can easily destroy the crystal form of the luminescent body, reduce the luminescent performance, and cause the particle size distribution to be uneven, and produce many impurities or mixed phases. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned problems in the prior art and provide a method for obtaining a nano-scale nitride fluorescent material. The fluorescent material is prepared by deliberately using raw materials in a non-stoichiometric ratio. Under relatively mild conditions and without using a ball milling process that would destroy the luminescent properties of the fluorescent material particles, a nano-scale nitride fluorescent material is finally obtained.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A method for obtaining a nano-scale nitride fluorescent material comprises the following steps:

[0008] 1) Ca mSi alloy, EuSi alloy and AlN powder are uniformly mixed in a protective atmosphere at a molar ratio of (1-x):x:1, and then the uniformly mixed powder is sintered at a high temperature in an ammonia atmosphere to obtain an intermediate, wherein 1.2≤m≤1.4, 0.02≤x≤0.08;

[0009] 2) grinding the intermediate obtained in step 1), mixing the powder obtained after grinding with an oxalic acid solution and then ultrasonicating to obtain a mixture containing a precipitate;

[0010] 3) Filtering the mixture obtained in step 2) and drying it to obtain the nano-scale nitride fluorescent material.

[0011] The high temperature sintering temperature is 1600-1800° C., and the high temperature sintering time is 4-10 hours.

[0012] The nano-nitride fluorescent material has a chemical formula of Ca x Eu 1-x AlSiN3, wherein 0.02≤x≤0.08.

[0013] Preferably, x may be 0.05, and m may be 1.32.

[0014] The D50 median particle size of the nano-scale nitride fluorescent material is 80 nm to 100 nm.

[0015] Under the excitation of 450 nm light, the main peak position of the emission spectrum of the nano-nitride fluorescent material is 670-710 nm, and the quantum efficiency is 50%-70%.

[0016] The nano-scale nitride fluorescent material is used to prepare Mini LED devices.

[0017] The Mini LED device includes a Mini LED and the nano-scale nitride fluorescent material; the emission wavelength range of the Mini LED is 380 nm to 480 nm, and the plane size is 100 μm×100 μm.

[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0019] The present invention provides a method for obtaining a nano-scale nitride fluorescent material. The chemical formula of the nano-scale nitride fluorescent material can be expressed as: Ca x Eu 1-xAlSiN3, wherein 0.02≤x≤0.08; the D50 median particle size of the nano-scale nitride fluorescent material is 80 nm to 100 nm; under the excitation of 450 nm light, the main peak position of the emission spectrum of the nano-scale nitride fluorescent material is 670 nm to 710 nm, and the quantum efficiency is 50% to 70%. In the step of preparing the nano-scale nitride fluorescent material, non-stoichiometric raw materials are deliberately used to prepare the nano-scale nitride fluorescent material. Under relatively mild synthesis conditions without the use of a ball milling process that would destroy the luminescent properties of the fluorescent material particles, a nano-scale nitride fluorescent material for Mini LED device packaging is finally obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the emission spectrum of the sample obtained in Comparative Example 1 under 450 nm light excitation;

[0021] Figure 2 This is the emission spectrum of the sample obtained in Example 1 under 450 nm light excitation;

[0022] Figure 3 is the SEM image of the sample obtained in Example 1;

[0023] Figure 4 This is a physical picture of the sample obtained in Example 23 packaged as a Mini LED device. DETAILED DESCRIPTION

[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0025] The present invention provides a method for obtaining a nano-scale nitride fluorescent material. The chemical formula of the nano-scale nitride fluorescent material can be expressed as: Ca x Eu 1-x AlSiN3, wherein 0.02≤x≤0.08; the D50 median particle size of the nano-scale nitride fluorescent material is between 80 nm and 100 nm; under the excitation of 450 nm light, the main peak position of the emission spectrum of the nano-scale nitride fluorescent material is between 670 nm and 710 nm, and the quantum efficiency value is between 50% and 70%.

[0026] In order to obtain the above-mentioned nano-scale nitride fluorescent material, the following steps are particularly adopted:

[0027] Step (A): Resuspend the chemical composition of Ca mThe Si alloy, the alloy with the chemical composition of EuSi and the AlN powder are uniformly mixed in a protective atmosphere at a molar ratio of (1-x):x:1, and then the uniformly mixed powder is sintered at a high temperature in an ammonia atmosphere with a certain pressure to obtain an intermediate, wherein 1.2≤m≤1.4, 0.02≤x≤0.08;

[0028] Step (B): grinding the intermediate obtained in step (A), mixing the powder obtained after grinding with an oxalic acid solution in a container, placing the container in an ultrasonic cleaning machine for ultrasonic treatment, and obtaining a solution containing a precipitate;

[0029] Step (C): The solution containing the precipitate obtained in step (B) is filtered through a filter membrane, and the residue on the filter membrane after the filtration is removed and dried to finally obtain a chemical formula represented by Ca x Eu 1-x Nano-scale nitride fluorescent material of AlSiN3 (where 0.02≤x≤0.08).

[0030] In the above step (A), Ca m The purity of Si alloy, EuSi alloy and AlN powder is not less than 99.5%, among which, 1.2≤m≤1.4

[0031] In the above step (A), the protective atmosphere is one or both of nitrogen and argon. In some embodiments provided by the present invention, the protective atmosphere is preferably nitrogen.

[0032] In the above step (A), the temperature of the high temperature solid phase reaction is between 1600 and 1800° C., and the time of the high temperature solid phase reaction is between 4 and 10 hours under the pressure of 1 MPa of the ammonia atmosphere.

[0033] In the above step (A), the temperature of the high-temperature solid phase is preferably 1600-1800°C, under an ammonia atmosphere with a pressure of 1 MPa; in some embodiments provided by the present invention, the temperature of the high-temperature solid phase is preferably 1700°C.

[0034] The high temperature solid phase time in the above step (A) is preferably 4 to 10 hours, more preferably 5 to 8 hours; in some embodiments provided by the present invention, the high temperature solid phase time is preferably 6 hours.

[0035] In the above step (A), the mixing process can be carried out in an environment familiar to those skilled in the art without any special restrictions, and a glove box is preferred in the present invention. The sintering process can be carried out in an environment familiar to those skilled in the art without any special restrictions, and a high-temperature furnace is preferred in the present invention. After the above sintering reaction is carried out, the intermediate can be obtained by cooling the furnace to room temperature.

[0036] In the above step (B), the mass ratio of powder to oxalic acid is 1:10, the concentration of oxalic acid is 0.5 mol / L, and the ultrasonic treatment time is 1 h.

[0037] In the above step (B), the ultrasonic treatment equipment can be any equipment familiar to those skilled in the art without any special limitation. In the present invention, an ultrasonic cleaning machine is preferred, and the power of the ultrasonic treatment is 50W.

[0038] In the above step (B), the pore size of the filter membrane is 50 nm, the drying temperature is 50° C., and the drying time is 3 h.

[0039] In Example 1 of the present invention, m is preferably 1.32, and x is preferably 0.05; in Examples 2 to 8 of the present invention, m is preferably 1.2, and x is preferably 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, and 0.08; in Examples 9 to 15 of the present invention, m is preferably 1.3, and x is preferably 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, and 0.08; in other Examples 16 to 22 of the present invention, m is preferably 1.4, and x is preferably 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, and 0.08;

[0040] The light-emitting device comprises a Mini LED and a fluorescent conversion material, wherein the Mini LED can emit light in the wavelength range of 380 nm to 480 nm, the plane size is 100 μm×100 μm, and the fluorescent conversion material at least comprises the above-mentioned step synthesized, the chemical formula of which can be expressed as Ca x Eu 1-x Nano-scale nitride fluorescent material of AlSiN3 (where 0.02≤x≤0.08).

[0041] The raw materials used in the following comparative examples and embodiments are all commercially available.

[0042] Comparative Example 1

[0043] Follow the steps below to make it:

[0044] CaSi alloy, EuSi alloy and AlN were mixed in a nitrogen atmosphere at a ratio of 0.95:0.05:1, and then the mixed powder was put into a crucible, and then the crucible was put into a high-temperature furnace and sintered at 1700℃ for 6h in an ammonia atmosphere with a pressure of 1MPa. Finally, a material with a theoretical chemical composition of Ca 0.95 Eu 0.05 AlSiN3 material.

[0045] The luminescence performance of the material obtained in Comparative Example 1 was tested using a fluorescence spectrometer, and its emission spectrum is as follows: Figure 1 As described. The results show that under 450 nm light excitation, the main peak of the emission spectrum of the material obtained in Comparative Example 1 is located at 655 nm. The D50 median particle size of the obtained material was tested using a laser particle size analyzer. Since a conventional high-temperature solid-phase reaction was used, the D50 median particle size of the final obtained material was 12.445 μm. Obviously, this value is extremely large and cannot be applied to the packaging of Mini LED devices at all. The sample was tested using a quantum efficiency tester. Since no destructive ball milling treatment was performed, the quantum efficiency of the sample was relatively high at 71.7% under 450 nm light excitation. See Table 1 for specific data.

[0046] That is, without using non-stoichiometric raw materials and oxalic acid for washing, the material obtained in Comparative Example 1 is not a nano-scale nitride fluorescent material.

[0047] Comparative Example 2

[0048] Follow the steps below to make it:

[0049] Step (A): CaSi alloy, EuSi alloy and AlN are mixed in a nitrogen atmosphere at a ratio of 0.95:0.05:1, and then the mixed powder is placed in a crucible, and then the crucible is placed in a high-temperature furnace, and sintered at 1700°C for 6 hours in an ammonia atmosphere with a pressure of 1MPa, and finally a theoretical chemical composition of Ca 0.95 Eu 0.05 AlSiN3 material.

[0050] Step (B): Take a theoretical chemical composition of Ca obtained in step (A) 0.95 Eu 0.05 50 g of AlSiN3 material was placed in a 200 ml ball mill, and 100 g of agate grinding balls were placed in the ball mill. The ball mill was installed in the ball mill, and the ball mill speed was set to 600 rpm. The ball mill was started and milled for 4 h. The ball mill was stopped and a theoretical chemical composition of Ca was obtained. 0.95 Eu 0.05 The AlSiN3 material is taken out from the ball mill to obtain a ball milled material with a theoretical chemical composition of Ca 0.95 Eu 0.05 AlSiN3 material.

[0051] The luminescence performance of the material obtained in Comparative Example 2 was tested using a fluorescence spectrometer. Due to the ball milling treatment, the surface of the obtained sample was destroyed, and more defects were generated on the surface of the sample, which caused a certain displacement of the emission spectrum of the sample. Finally, under 450 nm light excitation, the main peak of the emission spectrum of the material obtained in Comparative Example 2 was located at 660 nm. The D50 median particle size of the obtained material was tested using a laser particle size analyzer. Due to the long-term ball milling treatment, the D50 median particle size of the final obtained material was 1.152 μm. Obviously, after ball milling, the median particle size of the sample decreased significantly. The median particle size of the sample can basically meet the packaging of Mini LED devices. However, the sample was tested using a quantum efficiency tester. The results showed that due to the destructive ball milling treatment, the quantum efficiency of the sample was low at 35.1% under 450 nm light excitation, which means that the light efficiency of the Mini LED device encapsulated with the material obtained in Comparative Example 2 will be poor. See Table 1 for specific data.

[0052] That is, the material obtained in Comparative Example 2 is not a nano-scale nitride fluorescent material.

[0053] Comparative Example 3

[0054] Follow the steps below to make it:

[0055] Step (A): Resuspend the chemical composition of Ca 1.15 The Si alloy, the alloy with the chemical composition of EuSi and the AlN powder are mixed uniformly in a nitrogen atmosphere at a molar ratio of 0.95:0.05:1, and then the uniformly mixed powder is loaded into a crucible, and then the crucible is loaded into a high-temperature furnace, and sintered at 1700° C. for 6 hours in an ammonia atmosphere with a pressure of 1 MPa to obtain an intermediate;

[0056] Step (B): Grinding the intermediate obtained in step (A), mixing the powder obtained after grinding with a 0.5 mol / L oxalic acid solution in a container at a mass ratio of 1:10, and then placing the container in an ultrasonic cleaning machine with a power of 50 W for 1 hour to finally obtain a solution containing a precipitate;

[0057] Step (C): The solution containing the precipitate obtained in step (B) is filtered through a filter membrane with a pore size of 50 nm, and the residue on the filter membrane after the filtration is removed, placed in an oven, and dried at 50° C. for 3 hours to finally obtain a solid powder material.

[0058] Compared with Comparative Example 1, the chemical composition selected in Comparative Example 3 is Ca 1.15 Si alloy, rather than the alloy with the chemical composition of CaSi used in Comparative Example 1. This means that for Comparative Example 3, the raw materials used are non-stoichiometric. Theoretically, Ca1.15 Si reacts with ammonia in a high temperature furnace to obtain Ca3N2 and Si3N4, which in turn react with EuN (the total of EuSi reacting with ammonia) and AlN to finally obtain Ca 0.95 Eu 0.05 AlSiN3. But due to Ca 1.15 The Ca in Si alloy is excessive, that is, in the process of reaction with ammonia, excessive Ca3N2 will be produced, and the excessive Ca3N2 will prevent the occurrence of solid phase reaction, resulting in the solid particles obtained in the high-temperature solid phase reaction cannot grow too large, and the D50 median particle size is even only nanometers. The excess Ca3N2 is washed with oxalic acid, decomposed, and then filtered and dried. In the end, only fluorescent materials (solid particles cannot grow too large) are left in the solid powder.

[0059] The D50 median particle size of the material obtained in Comparative Example 3 was tested using a laser particle size analyzer, and the median particle size value was 933 nm. Obviously, the above steps can indeed obtain a nano-nitride phosphor, and the median particle size of the phosphor can meet the packaging of Mini LED devices. The luminescence performance of the material obtained in Comparative Example 3 was tested using a fluorescence spectrometer. Since it has not been ball-milled, the micro-nano characteristics of the sample have caused its (structure) energy level band gap to change. Under 450 nm light excitation, the main peak of the emission spectrum is located at 661 nm. The sample was tested using a quantum efficiency tester, and the results showed that due to the lack of destructive ball milling, the quantum efficiency of the sample was high at 55.2% under 450 nm light excitation. See Table 1 for specific data.

[0060] That is, the material obtained in Comparative Example 3 is a nano-scale nitride fluorescent material, but the median particle size is relatively high.

[0061] Comparative Example 4

[0062] Follow the steps below to make it:

[0063] Step (A): Resuspend the chemical composition of Ca 1.45 The Si alloy, the alloy with the chemical composition of EuSi and the AlN powder are mixed uniformly in a nitrogen atmosphere at a molar ratio of 0.95:0.05:1, and then the uniformly mixed powder is loaded into a crucible, and then the crucible is loaded into a high-temperature furnace, and sintered at 1700° C. for 6 hours in an ammonia atmosphere with a pressure of 1 MPa to obtain an intermediate;

[0064] Step (B): Grinding the intermediate obtained in step (A), mixing the powder obtained after grinding with a 0.5 mol / L oxalic acid solution in a container at a mass ratio of 1:10, and then placing the container in an ultrasonic cleaning machine with a power of 50 W for 1 hour to finally obtain a solution containing a precipitate;

[0065] Step (C): The solution containing the precipitate obtained in step (B) is filtered through a filter membrane with a pore size of 50 nm, and the residue on the filter membrane after the filtration is removed, placed in an oven, and dried at 50° C. for 3 hours to finally obtain a solid powder material.

[0066] Compared with Comparative Example 1, the chemical composition selected in Comparative Example 4 is Ca 1.45 Si alloy, rather than the alloy with the chemical composition of CaSi used in Comparative Example 1. This means that for Comparative Example 4, the raw materials used are non-stoichiometric. Theoretically, Ca 1.45 Si reacts with ammonia in a high temperature furnace to obtain Ca3N2 and Si3N4, which in turn react with EuN (the total of EuSi reacting with ammonia) and AlN to finally obtain Ca 0.95 Eu 0.05 AlSiN3. But due to Ca 1.45 The Ca in the Si alloy is more excessive (compared to comparative example 3), that is, in the process of reacting with ammonia, more excessive Ca3N2 will be produced, and more excessive Ca3N2 will prevent the occurrence of solid phase reaction, resulting in the inability of the solid particles obtained in the high-temperature solid phase reaction to grow larger, and the D50 median particle size is even only nanometers. The excess Ca3N2 is washed with oxalic acid, decomposed, and then filtered and dried. In the final solid powder, only the fluorescent material (solid particles cannot grow larger) is left.

[0067] The D50 median particle size of the material obtained in Comparative Example 4 was tested using a laser particle size analyzer, and the median particle size value was 57 nm. Obviously, the above steps can indeed obtain a nano-nitride phosphor, and the median particle size of the phosphor can meet the packaging of Mini LED devices. The luminescence performance of the material obtained in Comparative Example 4 was tested using a fluorescence spectrometer. Since it has not been ball-milled, the micro-nano characteristics of the sample have caused its (structure) energy level band gap to change. Under 450 nm light excitation, the main peak of the emission spectrum is located at 711 nm. The sample was tested using a quantum efficiency tester, and the results showed that due to the lack of destructive ball milling, the quantum efficiency of the sample was high at 57.3% under 450 nm light excitation. See Table 1 for specific data.

[0068] That is, the material obtained in Comparative Example 4 is a nano-scale nitride fluorescent material. However, the median particle size of the material obtained in Comparative Example 4 is too small, resulting in a too small bulk density of the sample, which is not convenient to store.

[0069] Comparative Example 5

[0070] Step (A): mixing an alloy having a chemical composition of CaSi, an alloy having a chemical composition of EuSi and AlN powder in a molar ratio of 0.95:0.05:1 under a nitrogen atmosphere, then charging the uniformly mixed powder into a crucible, charging the crucible into a high-temperature furnace, and sintering at 1700° C. for 6 hours under an ammonia atmosphere with a pressure of 1 MPa to obtain an intermediate;

[0071] Step (B): Grinding the intermediate obtained in step (A), mixing the powder obtained after grinding with a 0.5 mol / L oxalic acid solution in a container at a mass ratio of 1:10, and then placing the container in an ultrasonic cleaning machine with a power of 50 W for 1 hour to finally obtain a solution containing a precipitate;

[0072] Step (C): The solution containing the precipitate obtained in step (B) is filtered through a filter membrane with a pore size of 50 nm, and the residue on the filter membrane after the filtration is removed, placed in an oven, and dried at 50° C. for 3 hours to finally obtain a solid powder material.

[0073] Comparative Example 5 uses an alloy with a chemical composition of CaSi, and does not have the non-stoichiometric ratio problem of Comparative Example 3 / 4. However, Comparative Example 5 uses an oxalic acid washing process, and washing will obviously remove the tiny particles in the obtained material, which will theoretically increase the median particle size of the sample.

[0074] The D50 median particle size of the material obtained in Comparative Example 5 was tested using a laser particle size analyzer, and the median particle size value was 16.701 μm. The median particle size of the phosphor cannot meet the packaging of Mini LED devices. The luminescence performance of the material obtained in Comparative Example 5 was tested using a fluorescence spectrometer. Due to the lack of ball milling treatment, the main peak of the emission spectrum is located at 656 nm under 450 nm light excitation. The sample was tested using a quantum efficiency tester, and the results showed that due to the lack of destructive ball milling treatment, the quantum efficiency of the sample was high at 76.3% under 450 nm light excitation. See Table 1 for specific data.

[0075] That is, the material obtained in Comparative Example 5 is not a nano-scale nitride fluorescent material.

[0076] Example 1

[0077] Follow the steps below to make it:

[0078] Step (A): Resuspend the chemical composition of Ca 1.32 The Si alloy, the alloy with the chemical composition of EuSi and the AlN powder are mixed uniformly in a nitrogen atmosphere at a molar ratio of 0.95:0.05:1, and then the uniformly mixed powder is loaded into a crucible, and then the crucible is loaded into a high-temperature furnace, and sintered at 1700° C. for 6 hours in an ammonia atmosphere with a pressure of 1 MPa to obtain an intermediate;

[0079] Step (B): Grinding the intermediate obtained in step (A), mixing the powder obtained after grinding with a 0.5 mol / L oxalic acid solution in a container at a mass ratio of 1:10, and then placing the container in an ultrasonic cleaning machine with a power of 50 W for 1 hour to finally obtain a solution containing a precipitate;

[0080] Step (C): The solution containing the precipitate obtained in step (B) is filtered through a filter membrane with a pore size of 50 nm, and the residue on the filter membrane after the filtration is removed, placed in an oven, and dried at 50° C. for 3 hours to finally obtain a solid powder material.

[0081] Compared with Comparative Example 1, the chemical composition selected in Example 1 is Ca 1.32 Si alloy, rather than the alloy with the chemical composition of CaSi used in Comparative Example 1. This means that for Comparative Example 1, the raw materials used are non-stoichiometric. Theoretically, Ca 1.32 Si reacts with ammonia in a high temperature furnace to obtain Ca3N2 and Si3N4, which in turn react with EuN (the total of EuSi reacting with ammonia) and AlN to finally obtain Ca 0.95 Eu 0.05 AlSiN3. Due to Ca 1.32 The amount of Ca in the Si alloy is appropriate (compared to 3 / 4 of the comparative example), that is, in the process of reacting with ammonia, an appropriate amount of Ca3N2 will be produced, and the appropriate amount of Ca3N2 will prevent the occurrence of solid phase reaction, but the degree of preventing the reaction is appropriate, which ultimately leads to the solid particle size obtained in the high-temperature solid phase reaction meeting the packaging requirements of Mini LED devices and the main peak position of the quantum efficiency and emission spectrum being appropriate. The excess Ca3N2 is washed with oxalic acid, decomposed, and then filtered and dried, and only fluorescent materials with a suitable median particle size remain in the final solid powder.

[0082] The luminescence performance of the material obtained in Example 1 was tested using a fluorescence spectrometer. The results are as follows: Figure 2 As shown in Figure 2, the micro-nano-scale particle size characteristics of the sample lead to changes in the energy band gap (in the structure). Under 450 nm light excitation, the main peak of the emission spectrum is located at 690 nm. Figure 3The SEM image of the sample shows that the particle size of the sample is relatively small. The D50 median particle size of the material obtained in Example 1 was measured using a laser particle size analyzer, and the median particle size value was 90 nm.

[0083] Compared with Example 1 and Comparative Example 5, both use oxalic acid washing process. The difference between the two is that Comparative Example 5 uses a stoichiometric ratio of CaSi alloy raw material, while Example 1 uses a non-stoichiometric ratio of CaSi alloy raw material. 1.32 Si alloy raw materials, which ultimately leads to a large difference in the D50 median particle size values ​​of the two. The D50 median particle size of the material obtained in Comparative Example 5 is 16.701 μm, while that of Example 1 is 90 nm. The reason is as described above, that is, Comparative Example 5 uses a stoichiometric CaSi alloy raw material. During the high-temperature sintering process, all the raw materials have reacted and a single product (fluorescent material) is finally generated; while in Example 1, a non-stoichiometric CaSi alloy raw material is used. 1.32 Si alloy raw materials, Ca 1.32 In the Si alloy, excess Ca will react with ammonia to generate (excess Ca3N2 that cannot further participate in the reaction). The excess Ca3N2 will wrap around the newly generated fluorescent material particles, resulting in the inability of the fluorescent material particles to grow further. That is, the excess Ca3N2 acts as a barrier layer to prevent further high-temperature solid-phase reaction, which ultimately leads to a significant difference in the D50 median particle size of the fluorescent material obtained in Example 1 compared with that in Comparative Example 5.

[0084] Obviously, by adopting the above steps, a nano-scale nitride phosphor can be obtained, and the median particle size of the phosphor can meet the packaging of Mini LED devices. The results of testing the sample using a quantum efficiency tester show that due to the lack of destructive ball milling treatment, the quantum efficiency of the sample is relatively high, at 69.9% under 450 nm light excitation. See Table 1 for specific data.

[0085] That is, the material obtained in Example 1 is a nano-scale nitride fluorescent material with a D50 median particle size between 80 nm and 100 nm, an emission spectrum with a main peak position between 670 nm and 710 nm under the excitation of 450 nm light, and a quantum efficiency value between 50% and 70%.

[0086] Embodiments 2 to 8

[0087] Follow the steps below to make it:

[0088] Step (A): Resuspend the chemical composition of Ca 1.2The Si alloy, the alloy with the chemical composition of EuSi and the AlN powder were mixed uniformly in a nitrogen atmosphere at a molar ratio of 0.98:0.02:1 (Example 2), 0.97:0.03:1 (Example 3), 0.96:0.04:1 (Example 4), 0.95:0.05:1 (Example 5), 0.94:0.06:1 (Example 6), 0.93:0.07:1 (Example 7), and 0.92:0.08:1 (Example 8), and then the uniformly mixed powders were respectively charged into crucibles, and then the crucibles were charged into a high-temperature furnace, and sintered at 1700° C. for 6 hours in an ammonia atmosphere with a pressure of 1 MPa to obtain different intermediates;

[0089] Step (B): Grinding the different intermediates obtained in step (A), mixing the powders obtained after grinding with a 0.5 mol / L oxalic acid solution in a container at a mass ratio of 1:10, and then placing the container in an ultrasonic cleaning machine with a power of 50 W for 1 hour to finally obtain solutions containing precipitates;

[0090] Step (C): The different solutions containing precipitates obtained in step (B) are filtered through a filter membrane with a pore size of 50 nm. The residue on the filter membrane after filtration is removed, placed in an oven, and dried at 50° C. for 3 hours to finally obtain different solid powder materials.

[0091] Compared with Comparative Example 1, the chemical components selected in Examples 2 to 8 are Ca 1.2 Si alloy, rather than the alloy with the chemical composition of CaSi used in Comparative Example 1. This means that for Comparative Example 1, the raw materials used are non-stoichiometric. Theoretically, Ca 1.2 Si reacts with ammonia in a high temperature furnace to obtain Ca3N2 and Si3N4, which in turn react with EuN (the product of EuSi reacting with ammonia) and AlN to finally obtain Eu-doped CaAlSiN3. 1.2 The amount of Ca in the Si alloy is appropriate (compared to 3 / 4 of the comparative example), that is, in the process of reacting with ammonia, an appropriate amount of Ca3N2 will be produced, and the appropriate amount of Ca3N2 will prevent the occurrence of solid phase reaction, but the degree of preventing the reaction is appropriate, which ultimately leads to the solid particle size obtained in the high-temperature solid phase reaction meeting the packaging requirements of Mini LED devices and the main peak position of the quantum efficiency and emission spectrum being appropriate. The excess Ca3N2 is washed with oxalic acid, decomposed, and then filtered and dried, and only fluorescent materials with a suitable median particle size remain in the final solid powder.

[0092] The luminescence performance of the materials obtained in Examples 2 to 8 was tested using a fluorescence spectrometer. The micro-nano particle size characteristics of the sample caused the energy level band gap (in the structure) to change. Under 450 nm light excitation, the main peaks of the emission spectrum were located at 670 nm (Example 2), 675 nm (Example 3), 681 nm (Example 4), 685 nm (Example 5), 690 nm (Example 6), 698 nm (Example 7), and 702 nm (Example 8). The D50 median particle size of the materials obtained in Examples 2 to 8 was tested using a laser particle size analyzer, and the median particle size values ​​were 99 nm (Example 2), 96 nm (Example 3), 97 nm (Example 4), 93 nm (Example 5), 96 nm (Example 6), 92 nm (Example 7), and 90 nm (Example 8). Obviously, by using the above steps, a nano-nitride phosphor can be obtained, and the median particle size of the phosphor can meet the packaging of Mini LED devices. The results of testing the samples of Examples 2 to 8 using a quantum efficiency tester show that, due to the lack of destructive ball milling, the quantum efficiencies of the samples under 450nm light excitation are relatively high, namely 50.3% (Example 2), 57.2% (Example 3), 59.9% (Example 4), 67.1% (Example 5), 66.8% (Example 6), 54.2% (Example 7), and 51.1% (Example 8). See Table 1 for specific data.

[0093] That is, the material obtained in Examples 2 to 8 is a nano-scale nitride fluorescent material with a D50 median particle size between 80 nm and 100 nm, an emission spectrum with a main peak position between 670 nm and 710 nm under the excitation of 450 nm light, and a quantum efficiency value between 50% and 70%, which can meet the packaging requirements of Mini LED.

[0094] Embodiments 9 to 15

[0095] Follow the steps below to make it:

[0096] Step (A): Resuspend the chemical composition of Ca 1.3The Si alloy, the alloy with the chemical composition of EuSi and the AlN powder were mixed uniformly in a nitrogen atmosphere at a molar ratio of 0.98:0.02:1 (Example 9), 0.97:0.03:1 (Example 10), 0.96:0.04:1 (Example 11), 0.95:0.05:1 (Example 12), 0.94:0.06:1 (Example 13), 0.93:0.07:1 (Example 14) and 0.92:0.08:1 (Example 15), and then the uniformly mixed powders were respectively charged into crucibles, and then the crucibles were charged into a high-temperature furnace, and sintered at 1700° C. for 6 hours in an ammonia atmosphere with a pressure of 1 MPa to obtain different intermediates;

[0097] Step (B): Grinding the different intermediates obtained in step (A), mixing the powders obtained after grinding with a 0.5 mol / L oxalic acid solution in a container at a mass ratio of 1:10, and then placing the container in an ultrasonic cleaning machine with a power of 50 W for 1 hour to finally obtain solutions containing precipitates;

[0098] Step (C): The different solutions containing precipitates obtained in step (B) are filtered through a filter membrane with a pore size of 50 nm. The residue on the filter membrane after filtration is removed, placed in an oven, and dried at 50° C. for 3 hours to finally obtain different solid powder materials.

[0099] Compared with Comparative Example 1, the chemical components selected in Examples 9 to 15 are Ca 1.3 Si alloy, rather than the alloy with the chemical composition of CaSi used in Comparative Example 1. This means that for Comparative Example 1, the raw materials used are non-stoichiometric. Theoretically, Ca 1.3 Si reacts with ammonia in a high temperature furnace to obtain Ca3N2 and Si3N4, which in turn react with EuN (the product of EuSi reacting with ammonia) and AlN to finally obtain Eu-doped CaAlSiN3. 1.3 The amount of Ca in the Si alloy is appropriate (compared to 3 / 4 of the comparative example), that is, in the process of reacting with ammonia, an appropriate amount of Ca3N2 will be produced, and the appropriate amount of Ca3N2 will prevent the occurrence of solid phase reaction, but the degree of preventing the reaction is appropriate, which ultimately leads to the solid particle size obtained in the high-temperature solid phase reaction meeting the packaging requirements of Mini LED devices and the main peak position of the quantum efficiency and emission spectrum being appropriate. The excess Ca3N2 is washed with oxalic acid, decomposed, and then filtered and dried, and only fluorescent materials with a suitable median particle size remain in the final solid powder.

[0100] The luminescence performance of the materials obtained in Examples 9 to 15 was tested using a fluorescence spectrometer. The micro-nano particle size characteristics of the sample caused the energy level band gap (in the structure) to change. Under 450 nm light excitation, the main peaks of the emission spectrum were located at 671 nm (Example 9), 678 nm (Example 10), 685 nm (Example 11), 690 nm (Example 12), 695 nm (Example 13), 703 nm (Example 14), and 707 nm (Example 15). The D50 median particle size of the materials obtained in Examples 9 to 15 was tested using a laser particle size analyzer, and the median particle size values ​​were 88 nm (Example 9), 87 nm (Example 10), 86 nm (Example 11), 91 nm (Example 12), 92 nm (Example 13), 86 nm (Example 14), and 88 nm (Example 15). Obviously, by using the above steps, a nano-nitride phosphor can be obtained, and the median particle size of the phosphor can meet the packaging of Mini LED devices. The results of testing the samples of Examples 9 to 15 using a quantum efficiency tester show that, due to the lack of destructive ball milling treatment, the quantum efficiencies of the samples under 450 nm light excitation are relatively high, namely 54.4% (Example 9), 56.7% (Example 10), 59.2% (Example 11), 68.2% (Example 12), 60.3% (Example 13), 61.5% (Example 14), and 66.6% (Example 15). See Table 1 for specific data.

[0101] That is, the material obtained in Examples 9 to 15 is a nano-scale nitride fluorescent material with a D50 median particle size between 80 nm and 100 nm, an emission spectrum with a main peak position between 670 nm and 710 nm under the excitation of 450 nm light, and a quantum efficiency value between 50% and 70%, which can meet the packaging requirements of Mini LED.

[0102] Examples 16 to 22

[0103] Follow the steps below to make it:

[0104] Step (A): Resuspend the chemical composition of Ca 1.4The Si alloy, the alloy with the chemical composition of EuSi and the AlN powder were mixed uniformly in a nitrogen atmosphere at a molar ratio of 0.98:0.02:1 (Example 16), 0.97:0.03:1 (Example 17), 0.96:0.04:1 (Example 18), 0.95:0.05:1 (Example 19), 0.94:0.06:1 (Example 20), 0.93:0.07:1 (Example 21), and 0.92:0.08:1 (Example 22), and then the uniformly mixed powders were respectively charged into crucibles, and then the crucibles were charged into a high-temperature furnace, and sintered at 1700° C. for 6 hours in an ammonia atmosphere with a pressure of 1 MPa to obtain different intermediates;

[0105] Step (B): Grinding the different intermediates obtained in step (A), mixing the powders obtained after grinding with a 0.5 mol / L oxalic acid solution in a container at a mass ratio of 1:10, and then placing the container in an ultrasonic cleaning machine with a power of 50 W for 1 hour to finally obtain solutions containing precipitates;

[0106] Step (C): The different solutions containing precipitates obtained in step (B) are filtered through a filter membrane with a pore size of 50 nm. The residue on the filter membrane after filtration is removed, placed in an oven, and dried at 50° C. for 3 hours to finally obtain different solid powder materials.

[0107] Compared with Comparative Example 1, the chemical components selected in Examples 16 to 22 are Ca 1.4 Si alloy, rather than the alloy with the chemical composition of CaSi used in Comparative Example 1. This means that for Comparative Example 1, the raw materials used are non-stoichiometric. Theoretically, Ca 1.3 Si reacts with ammonia in a high temperature furnace to obtain Ca3N2 and Si3N4, which in turn react with EuN (the product of EuSi reacting with ammonia) and AlN to finally obtain Eu-doped CaAlSiN3. 1.4 The amount of Ca in the Si alloy is appropriate (compared to 3 / 4 of the comparative example), that is, in the process of reacting with ammonia, an appropriate amount of Ca3N2 will be produced, and the appropriate amount of Ca3N2 will prevent the occurrence of solid phase reaction, but the degree of preventing the reaction is appropriate, which ultimately leads to the solid particle size obtained in the high-temperature solid phase reaction meeting the packaging requirements of Mini LED devices and the main peak position of the quantum efficiency and emission spectrum being appropriate. The excess Ca3N2 is washed with oxalic acid, decomposed, and then filtered and dried, and only fluorescent materials with a suitable median particle size remain in the final solid powder.

[0108] The luminescence performance of the materials obtained in Examples 16 to 22 was tested using a fluorescence spectrometer. The micro-nano particle size characteristics of the sample caused the energy level band gap (in the structure) to change. Under 450 nm light excitation, the main peaks of the emission spectrum were located at 673 nm (Example 16), 682 nm (Example 17), 685 nm (Example 18), 693 nm (Example 19), 699 nm (Example 20), 705 nm (Example 21), and 710 nm (Example 22). The D50 median particle size of the materials obtained in Examples 16 to 22 was tested using a laser particle size analyzer, and the median particle size values ​​were 86 nm (Example 16), 86 nm (Example 17), 82 nm (Example 18), 81 nm (Example 19), 86 nm (Example 20), 85 nm (Example 21), and 90 nm (Example 22). Obviously, by using the above steps, a nano-nitride phosphor can be obtained, and the median particle size of the phosphor can meet the packaging of MiniLED devices. The results of testing the samples of Examples 16 to 22 using a quantum efficiency tester show that, due to the lack of destructive ball milling treatment, the quantum efficiencies of the samples under 450 nm light excitation are relatively high, namely 59.1% (Example 16), 59.4% (Example 17), 63.4% (Example 18), 66.7% (Example 19), 67.2% (Example 20), 50.9% (Example 21), and 50.4% (Example 22). See Table 1 for specific data.

[0109] That is, the material obtained in Examples 16 to 22 is a nano-scale nitride fluorescent material with a D50 median particle size between 80 nm and 100 nm, an emission spectrum with a main peak position between 670 nm and 710 nm under the excitation of 450 nm light, and a quantum efficiency value between 50% and 70%, which can meet the packaging requirements of Mini LED.

[0110] Embodiment 23

[0111] The chemical formula obtained in Example 1 is Ca 0.95 Eu 0.05 AlSiN3 nano-scale nitride fluorescent material is packaged with Mini LED with an emission wavelength of 450 nm and a plane size of 100 μm×100 μm. The specific packaging process is: 0.95 Eu 0.05 AlSiN3 nano-nitride fluorescent material and epoxy resin are mixed in a mass ratio of 1:3.75, and then coated on the surface of a Mini LED with an emission wavelength of 450 nm and a plane size of 100 μm×100 μm, and then cured at 150°C for 30 minutes to obtain a Mini LED device. Figure 4 A physical picture of the device obtained in Example 23 is given.

[0112] Table 1 Data table of material properties corresponding to comparative examples and examples

[0113]

[0114] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A method for obtaining a nano-scale nitride fluorescent material, characterized in that: The following steps are involved: 1) Ca m Si alloy, EuSi alloy and AlN powder are uniformly mixed in a protective atmosphere at a molar ratio of (1-x):x:1, and then the uniformly mixed powder is sintered at a high temperature in an ammonia atmosphere to obtain an intermediate, wherein 1.2≤m≤1.4, 0.02≤x≤0.08; 2) grinding the intermediate obtained in step 1), mixing the powder obtained after grinding with an oxalic acid solution and then ultrasonicating to obtain a mixture containing a precipitate; 3) Filtering the mixture obtained in step 2) and drying it to obtain the nano-scale nitride fluorescent material.

2. A method for obtaining a nano-scale nitride fluorescent material as claimed in claim 1, characterized in that: The high temperature sintering temperature is 1600-1800° C., and the high temperature sintering time is 4-10 hours.

3. A nano-scale nitride fluorescent material, characterized in that: Prepared by the method according to any one of claims 1 to 2.

4. A nano-scale nitride fluorescent material as claimed in claim 3, characterized in that: The chemical formula is Ca x Eu 1- x AlSiN3, wherein 0.02≤x≤0.

08.

5. The nano-scale nitride fluorescent material according to claim 3, characterized in that: The D50 median particle size of the nano-scale nitride fluorescent material is 80 nm to 100 nm.

6. The nano-scale nitride fluorescent material according to claim 3, characterized in that: Under the excitation of 450 nm light, the main peak position of the emission spectrum of the nano-nitride fluorescent material is 670-710 nm, and the quantum efficiency is 50%-70%.

7. The use of the nano-scale nitride fluorescent material according to claim 3, characterized in that: Used to prepare Mini LED devices.

8. A Mini LED device, characterized in that: It comprises a Mini LED and the nano-scale nitride fluorescent material as claimed in claim 3.

9. The Mini LED device according to claim 8, characterized in that: The emission wavelength range of the Mini LED is 380 nm to 480 nm.

10. The Mini LED device according to claim 8, characterized in that: The planar size of the Mini LED is 100 μm×100 μm.

Citation Information

Patent Citations

  • Method for preparing nitride red fluorescent powder

    CN101948688A

  • Alkaline earth nitride fluorescent powder and preparation method thereof

    CN102517000A

  • Luminous ceramic material as well as preparation method and application thereof

    CN105753480A

  • Synthetic method of high-nitrogen-content high-brightness nitrogen oxide fluorescent powder

    CN107312538A